ANALISIS KEBIJAKAN PEMERINTAH KOTA SURAKARTA MENGENAI PASAR TRADISIONAL DAN PASAR MODERN - Setyawan, Eka Indriya; Samudro, Bhimo Rizky; Pratama, Yogi Pasca (EP FEB UNS, 2015)
This research aimed to see and review policy trend government of Surakarta toward traditional market and modern market on Surakarta. The next analyze to see trend of Surakarta Government toward traditional and moder market. Measures used to know trend of Surakarta government are see policies established by local regulations. This research uses data from the literature are taken from the literature that supports. Analysis used at this research are descriptive analysis with way being narrative a variety of data found in the field and the compared with existing theory. Based on the descriptive analysis, policy issued from government of Surakarta, especially last policy about dismissal licensing for establishment modern shop and various program on traditional market development include market revitalisation that will be done for all markets in Surakarta. This matter showed a tendency to further strengthen the Surakarta municipal government policies to spur the existence and development of traditional market, by limiting the development of modern market. Keywords: Market, Traditional Market, Modern Market, Public policyJEL Classification: P16, P 35, P47